2015
DOI: 10.3923/tmr.2015.97.105
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Blood Parameters of High Salt Loaded Rats Following Administration of Moringa oleifera Leaf Extract

Abstract: High salt loading is associated with myriad deleterious effects including alterations in blood parameters, cardiovascular risk and sudden death. This study explored the impact of Moringa oleifera on some blood parameters in high salt loaded rats. Twenty four male albino Wistar rats were assigned into 4 groups of 6 rats each. They were fed on either control diet, high salt diet (8% NaCl diet+1% NaCl drinking water) and/or Moringa extract (600 mg kgG 1 b.wt. orally, once daily) ad libitum for 6 weeks. Blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…These findings might be due to the presence of vitamins, and iron in Aloe vera. A similar finding was observed in a study conducted by Ani et al 18 and Ofem et al 20 Group C demonstrated a significant increase in the mean MCH to nearly 18 pg during the same period indicating that Aloe vera helped improve the haemoglobin concentration in PHZ-treated rats. Kolawole and associates 22 showed that the MCH level was significantly decreased in the PHZ-treated only group than that in the normal control group which is consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 87%
“…These findings might be due to the presence of vitamins, and iron in Aloe vera. A similar finding was observed in a study conducted by Ani et al 18 and Ofem et al 20 Group C demonstrated a significant increase in the mean MCH to nearly 18 pg during the same period indicating that Aloe vera helped improve the haemoglobin concentration in PHZ-treated rats. Kolawole and associates 22 showed that the MCH level was significantly decreased in the PHZ-treated only group than that in the normal control group which is consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 87%
“…However, it provides a cardioprotective effect by reducing nocturnal heart rate increasing ejection volume and cardiac output ( Randriamboavonjy et al, 2016 ). Another study by Ofem et al (2015) reported that aqueous MO leaf extracts might resolve the abnormalities in hematology parameters in rats treated with a high-salt diet such as white blood cells, red blood cells, platelet counts, packed cell volume, lymphocytes, platelet large cell ratio, mean platelet volume, and platelet distribution width (PDW).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have been reported for anemic human patients by Suzana et al,. (2017) and for albino rabbits fed Moringa Ofem et al, (2015). The RDWc is a range of volume and size of RBCs and is a valid indicator of anisocytosis of RBCs.…”
Section: Discussionmentioning
confidence: 99%